Spectrum of Medicolegal Cases in Physical Injury at Peoples Medical College Hospital, Nawabshah, Shaheed Benazirabad, Sindh, Pakistan (Medical Forum Monthly, 2024)
Objective: The purpose behind this study was to determine the spectrum of medicolegal cases in physical injury at Peoples Medical College Hospital, Nawabshah, Shaheed Benazirabad, Sindh, Pakistan.Study Design: Prospective / observational studyPlace and Duration of Study: This study was conducted at the at a tertiary care Peoples Medical College Hospital, Nawabshah, Shaheed Benazirabad, Sindh, Pakistan from 2014 to 2018.Materials and Methods: The study has been conducted through a convenience sampling technique on autopsied 259 males and females between the periods of six years to observe the frequency and location of physical injury leads to death among different age groups. Ethical consent was taken from family member and hospital before doing autopsy and use of its findings for study purpose. A structured questionnaire was used to collect the objective specific data and we used SPSS version 21 for data entry and analysis.Results: Our study has male predominance (95.75%, N = 248) with more autopsied were performed in rural areas (66.02, N = 171).More than 77% (N = 202) autopsied persons did not had traumatic bony lesion during examination. The most commonly used weapon was hard blunt type 76.47% (N = 39/51) while comparatively less people were killed due to firearm injury (17.64%).Conclusion: The spectrum of medicolegal cases is quite variable in people presenting at Peoples Medical College Hospital, Nawabshah, Shaheed Benazirabad, Sindh, Pakistan in which most of them were killed due to blunt weapon.